2012
DOI: 10.1007/s11434-012-5447-x
|View full text |Cite
|
Sign up to set email alerts
|

Preparation, characterization and photodegradation of methylene blue based on TiO2 microparticles modified with thiophene substituents

Abstract: The new microparticles, 2-formylthiophene (FT)/TiO 2 and (E)-1,2-bis(5-formyl-2-thienyl) ethylene (EBFTE)/TiO 2 were synthesized with a silane coupling agent. The prepared TiO 2 composites were characterized using Ultraviolet-Vis absorption (UV-Vis), X-ray diffraction (XRD), scanning electron microscope (SEM) and thermogravimetric analyzer (TGA). Methylene blue was used as a model material to examine the photocatalytic activities of the prepared catalysts under both Ultraviolet-Vis (UV) and visible (Vis) light… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Furthermore, Figure 6 shows that Ag-TiO 2 thin films showed an important increase in the photocatalytic activity under UV (near 35%); these results could be due to the silver aggregates deposited on the TiO 2 surface that can accumulate charge and accept electrons inside the semiconductor. The accumulation of electrons can reduce the carrier's recombination increasing generation of reactive oxygen species, and besides, Ag particle on TiO 2 can change and a collective oscillation can be generated, which is known as localized surface plasmon resonance (SPR) [49]; according to other reports, silver particles exhibit collective oscillation of their electrons in the conduction band, and it is suggested that the association between the semiconductor and the metal can increase photocatalytic activity, which coincides with the results obtained in this work [50]. Pseudo-first-order model was applied to kinetic data of Figure 6.…”
mentioning
confidence: 99%
“…Furthermore, Figure 6 shows that Ag-TiO 2 thin films showed an important increase in the photocatalytic activity under UV (near 35%); these results could be due to the silver aggregates deposited on the TiO 2 surface that can accumulate charge and accept electrons inside the semiconductor. The accumulation of electrons can reduce the carrier's recombination increasing generation of reactive oxygen species, and besides, Ag particle on TiO 2 can change and a collective oscillation can be generated, which is known as localized surface plasmon resonance (SPR) [49]; according to other reports, silver particles exhibit collective oscillation of their electrons in the conduction band, and it is suggested that the association between the semiconductor and the metal can increase photocatalytic activity, which coincides with the results obtained in this work [50]. Pseudo-first-order model was applied to kinetic data of Figure 6.…”
mentioning
confidence: 99%